The utility of ultrasound superb microvascular imaging for evaluation of breast tumour vascularity: comparison with colour and power Doppler imaging regarding diagnostic performance. Issue 3 (March 2018) - Park, A.Y.; Seo, B.K.; Woo, O.H.; Jung, K.S.; Cho, K.R.; Park, E.K.; Cha, S.H.; Cha, J.
Abstract : Aim: To investigate the utility of superb microvascular imaging (SMI) for evaluating the vascularity of breast masses in comparison with colour or power Doppler ultrasound (US) and the effect on diagnostic performance. Materials and methods: A total of 191 biopsy-proven masses (99 benign and 92 malignant) in 166 women with greyscale, colour Doppler, power Doppler, and SMI images were enrolled in this retrospective study. Three radiologists analysed the vascular images using a three-factor scoring system to evaluate the number, morphology, and distribution of tumour vessels. They assessed the Breast Imaging-Reporting and Data System categories for greyscale US alone and combinations of greyscale US and each type of vascular US. The Kruskal–Wallis test was performed and the area under the receiver-operating characteristic curve (AUC) measured. On SMI, vascular scores were compared between benign and malignant masses and the optimal cut-off value for the overall score was determined. Results: SMI showed higher vascular scores than colour or power Doppler US and malignant masses had higher scores than benign masses ( p <0.001). The diagnostic performance of the combination of greyscale US and SMI was higher than those of greyscale US alone and greyscale and colour or power Doppler US (AUC, 0.815 versus 0.774, 0.789, 0.791; p <0.001). The optimal cut-off value of the overall vascular score was 5 with a sensitivity of 82.3% and a specificity of 65.3% (AUC, 0.808). Conclusion: SMI is superior to colour or power Doppler US for characterising the vascularity in breast masses and improving diagnostic performance. Highlights: Tumour angiogenesis plays an essential role in tumour development and metastasis of breast cancers. Superb Microvascular Imaging (SMI) is an innovative Doppler technique for the visualization of microvessels with low-velocity flows. SMI is superior to conventional colour or power Doppler US in identifying and characterizing microvessels in solid breast masses. The combined use of gray-scale ultrasonography and SMI can improve the diagnostic performance in distinguishing malignant from benign breast masses.